The impact of school curricula on addressing extremism - Al-Tai, Dr. Izzat Hussein Ali Al-Tai; Al-Mufarji, Prof. Dr. Saddam Hussein Kadhim Al-Mufarji (Sulaimani Journal for Humanities, 2026)
Curricula, if carefully and strategically designed, can serve as the first line of defense against extremism and radicalization. They lay the intellectual and behavioral foundations that enable individuals to reject destructive ideologies and uphold the values of balance and moderation. For curricula to effectively fulfill this role, they must be flexible and adaptable, keeping pace with social and cultural developments and countering extremist ideas with sound educational methods. Teachers must also be trained to implement these curricula effectively, emphasizing practical applications through hands-on activities that reinforce the targeted values in students. Furthermore, coordination with families and community institutions is integral to the success of curricula in addressing extremism, as the surrounding environment plays a complementary role to that of the school. Therefore, developing curricula that meet the needs of the times and incorporating values that promote tolerance and moderation will contribute to building a safe, cohesive society, resilient against the dangers of extremism and radicalization. The importance of this research lies in its focus on developing and teaching students the foundations of scientific and critical thinking, which helps them analyze and refute extremist ideas. It also examines the role of curricula in addressing extremism and fanaticism, and in promoting values of tolerance, dialogue, and acceptance of others, thus mitigating extremism and fanaticism. The research aimed to achieve several objectives, most importantly: to reveal the impact of curricula in addressing extremism by correcting misconceptions and achieving social peace. The researchers used an inductive approach to arrive at sound scientific results that serve the research objectives. The research reached several conclusions, the most important of which are: Curricula are among the most important educational tools that contribute to shaping individual and societal awareness, and they play a prominent role in addressing extremism and fanaticism. They are considered a means of sound upbringing and developing values of tolerance, moderation, and respect for diversity. Curricula highlight the importance of peaceful coexistence among different cultures, which reduces exclusionary tendencies.
Keywords: Curricula; extremism; radicalism; social peace